2005
DOI: 10.1158/1055-9965.epi-05-0119
|View full text |Cite
|
Sign up to set email alerts
|

Allergies and the Risk of Pancreatic Cancer: A Meta-analysis with Review of Epidemiology and Biological Mechanisms

Abstract: Previous reports suggest that allergic disorders may protect against various types of cancer, but the association between history of allergy and pancreatic cancer risk has not been well studied. We did a systematic review and meta-analysis of published studies to evaluate the association of any type, and specific types, of allergy and the risk of pancreatic cancer. We did a comprehensive literature search using MEDLINE, PUBMED, and the ISI Web of Science databases to identify potential relevant case-control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 66 publications
(33 reference statements)
4
87
2
1
Order By: Relevance
“…Similar results were observed in other case-control 19,26 and cohort studies. 17 A recent metaanalysis by Gandini et al (2005) also provides additional support to our findings. We did not observe an association between asthma and pancreas cancer risk.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar results were observed in other case-control 19,26 and cohort studies. 17 A recent metaanalysis by Gandini et al (2005) also provides additional support to our findings. We did not observe an association between asthma and pancreas cancer risk.…”
Section: Discussionsupporting
confidence: 84%
“…13,23 Several studies have examined the association between a history of allergies and pancreas cancer risk. [12][13][14][15][16][17]19,[23][24][25][26][27][28] Among several case-control and cohort studies, a significantly reduced risk was observed with a history of any type of allergy.…”
Section: Allergies and Pancreas Cancer Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk reductions were more distinct for this cancer site, by up to more than 50%. The pancreas is accessible to all of the cells required for a successful immunosurveillance, so the hypothesis of enhanced immunosurveillance seems to apply for this type of cancer [61]. The protective effect should be ascribed to the systemic effect of allergies, and not to any local reaction which takes place at the entry location of allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that examined the associations between allergies and pancreatic cancer have generated varying results. The findings from one meta-analysis showed that there was no associa-tion between asthma and risk of pancreatic cancer, 20 while the results from another, more recent, meta-analysis showed consistent inverse associations between asthma and risk of pancreatic cancer as well as between nasal allergies and risk of pancreatic cancer. 6 The findings from a recent cohort study, which used a nationwide database, revealed that the associations between allergies and cancer are site specific, and that patients with more than one allergic disease had lower cancer risks compared with those with only one allergic disease.…”
Section: Discussionmentioning
confidence: 97%